Advancing biological processing for valorization of plastic wastes. (December 2022) - Gluth, A.; Xu, Z.; Fifield, L.S.; Yang, B.
Abstract: The useful applications of plastics are as significant as the problems associated with their disposal. Current waste management strategies are ineffective at preventing the flow of plastics into landfills, wastewater treatment, and the environment. Despite the importance of recycling technologies, most plastics are used for consumables and are discarded after limited usage. Moreover, only certain plastics are recycled, and those that are generally yield lower value products. Discovering alternative routes for valorizing plastic wastes is essential. Emerging research involves the use of biocatalysts (i.e., enzymes and microorganisms) to produce valuable products like specialty polymers, biosurfactants, and drug precursors from these feedstocks. These bioprocesses commonly integrate physio-chemical pretreatments (to generate biologically reactive intermediates) and biological upgrading (to convert intermediates to products). Herein, publications that explore plastic deconstruction technologies and bioprocesses are reviewed with an emphasis on plastic waste valorization. Understanding how microorganisms metabolize the intermediates of plastic degradation and manage their inhibitory effects is a prerequisite for engineering bioprocesses. For these heterogeneous wastes, a paradigm shift from axenic cultivation of microorganisms to cultivation of microbial consortia may benefit conversion efficiency and stress resilience. Thus, a summary is provided for metabolic pathways and constituent enzymes required to synthesize biofuels, biomaterials, and chemicals from biologically reactive intermediates. Colossal challenges associated with the use of plastics as feedstocks for direct biological processing highlight the need for integrating physical, chemical, and biological technologies. Graphical abstract: Effective pretreatments may facilitate the biological processing of plastic wastes by maximizing the selective generation of biologically reactive intermediates that can be converted to value-added products. For plastics abbreviations, please refer to the sections hereafter. Image 1 Highlights: Challenges facing biological processing of plastic wastes are identified. Biological treatment alone is largely ineffective at processing plastic wastes. Mechanical, chemical, and radiologic conversion technologies can pretreat plastic. Plastic wastes incompatible with recycling are potential bioprocessing feedstocks. Bioprocesses provide unique routes for converting complex feedstocks to products.